(untitled) (Acta Scientiarum. Animal Sciences, 2018)
This study evaluated the effects of the rehydration and ensiling of corn grain with two geometric mean diameters (GMD) of 0.55 and 1.83 mm obtained by the diameter of the sieved used on the fermentation characteristics and chemical composition of the silage. The experimental design was completely randomized with two treatments and six replications, as follows: rehydrated fine-corn grain silage (RFS) and rehydrated coarse-corn grain silage (RCS). Ground corn was rehydrated with water to achieve moisture levels close to 350 g kg-1. There was no effect on the dry matter recovery, though the recovery rate was high, with values greater than 97% in both silages. The particle size influenced the fiber content, with lower values in the RFS. The acetic and lactic acid concentrations were higher in the RFS, but the pH of the silages did not change. Oxygen exposure changed the pH of silages to 4.25 and 4.38 for RFS and RCS, respectively. After opening the silos, the silages showed high aerobic stability after 90 hours, which resulted in lower deterioration and lesser loss of quality. The geometric mean diameter of corn grain affects the silage fermentative profile and nutritional value.